Intradermal acupuncture therapy and nursing care for a patient with insomnia after stroke (皮内针法应用于1例脑卒中后失眠患者的护理体会) - GAO Ya (高雅); LIU Guiying (刘桂英) (中西医结合护理, 2022)
Insomnia is the most common mental and emotional disease that occurs in stroke patients, and insomnia indirectly affects the recovery of nerve function and clinical prognosis in stroke patients, and may even lead to the recurrence of stroke. Intradermal acupuncture is a method of treating insomnia by inserting intradermal needle and fixing it in the skin or subcutaneous area of the acupuncture point, stimulating it for a long time to treat the disease, and adjusting the function of Qi and blood in the meridian organs. This article reviewed the treatment and nursing care of a patient with insomnia after stroke. On the basis of conventional treatment and nursing care, intradermal acupuncture was carried out to improve the sleep quality of the patient. (失眠在脑卒中患者好发的精神或情绪疾病中占首位, 失眠不但影响脑卒中患者神经功能恢复, 继而影响临床预后, 还可能引起脑卒中的复发。皮内针法是用皮内针刺入腧穴部位的皮内或皮下并加以固定, 从而进行持续刺激来达到治疗疾病目的的一种方法, 通过疏通经络、调理脏腑气血的功能以治疗失眠。本文总结1例脑卒中并发失眠患者的护理经验, 在常规失眠治疗、护理干预的基础上, 给予皮内针法护理, 改善患者睡眠质量。)